Thinking Framework Concept: A Decolonial Epistemological Proposal for the Current Latin-American Scenario - Soto Pimentel, Verónica (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2017)
The new crisis faced by Latin American governments of counter-hegemonic political projects – which had made important progress towards inclusion – against the (re) strengthening of a bloc of countries with neoliberal projects that have tended to aggravate regional social problems raises the question: how to break this return to the myth of Sisyphus? Based on the presuppositions of decolonial thinking, the proposed hypothesis is that this would be - partly due to- the presence of Eurocentric features in the construction of knowledge on social problems and their solution in the political projects that are discussed in the region. This paper proposes a categorization of the concept of a thinking framework in order to identify the presence of these features in the epistemological foundations of Latin American political projects, which would go unnoticed from categories derived from hegemonic forms of knowledge.